2021
DOI: 10.1002/nop2.972
|View full text |Cite
|
Sign up to set email alerts
|

Sleep status of psychiatric nurses: A survey from China

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…One study involving Chinese psychiatric nurses showed that night shift nurses have worse sleep, which leads to higher levels of burnout (Lyu et al . 2021 ). Another study of nurses in Spain revealed that night shift nurses lack confidence in their nursing ability (Gómez‐García et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study involving Chinese psychiatric nurses showed that night shift nurses have worse sleep, which leads to higher levels of burnout (Lyu et al . 2021 ). Another study of nurses in Spain revealed that night shift nurses lack confidence in their nursing ability (Gómez‐García et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising as night shifts disrupt one's biological rhythms and subject nurses to long-term fatigue. One study involving Chinese psychiatric nurses showed that night shift nurses have worse sleep, which leads to higher levels of burnout (Lyu et al 2021). Another study of nurses in Spain revealed that night shift nurses lack confidence in their nursing ability (G omez-Garc ıa et al 2016), likely resulting from their missed care plans and deprived sleep.…”
Section: Gender-specific Factors Associated With Burnoutmentioning
confidence: 99%
“…Nurses are prone to many sleep problems due to the nature of their profession (Zhan et al, 2020;Oteir et al, 2022). Insomnia prevalence in nurses was reported to be approximately 30 to 65.4% worldwide, and 37-63.9% in China (Pappa et al, 2020;Zhan et al, 2020;Lyu et al, 2022). Insomnia impairs individuals' cognitive, physical, and emotional functions, greatly reducing the quality of life and adversely affecting health (Fernandez-Mendoza et al, 2015;Li et al, 2015;Brownlow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorder has been a common health problem worldwide [ 9 , 10 ] and associated with a series of adverse health and social consequences [ 11 , 12 ]. It has been suggested that healthcare professionals, especially professional nurses, appeared to be more susceptible to sleep disorders than the general population [ 13 , 14 ]. The shift work schedule can disrupt circadian rhythms that lead to disrupted sleep schedules and severely impair sleep quality and quantity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality of professional nurses has been a concern and there is lots of research on it [ 14 ]. The overall prevalence of sleep problems among clinical nurses working in general hospitals in mainland China was found to be high, reporting an incidence of 55% [ 20 ].…”
Section: Introductionmentioning
confidence: 99%